4D-CT for Preoperative Localization of Abnormal Parathyroid Glands in Patients with Hyperparathyroidism: Accuracy and Ability to Stratify Patients by Unilateral versus Bilateral Disease in Surgery-Naïve and Re-Exploration Patients - Kelly, H.R. (AJNR Am J Neuroradiol, 2014)
BACKGROUND AND PURPOSE: 4D-CT is an emerging technique that uses high-resolution images, multiplanar reformats, and perfusion characteristics to identify abnormal parathyroid glands in patients with hyperparathyroidism. This study evaluates the accuracy of 4D-CT for localization and lateralization of abnormal parathyroid glands in preoperative planning for minimally invasive parathyroidectomy vs bilateral neck exploration at a tertiary referral center. MATERIALS AND METHODS: Radiology, pathology, and operative reports were retrospectively reviewed for 208 patients with hyperparathyroidism who underwent 4D-CT and parathyroid surgery between May 2008 and January 2012. 4D-CT performance in localizing side and site was determined by use of surgical and pathologic findings as a reference. RESULTS: Of 208 patients, 155 underwent initial surgery and 53 underwent re-exploration parathyroid surgery. No lesions were found in 8 patients (3.8%). A total of 284 lesions were found in 200 patients; 233 were correctly localized by 4D-CT (82.0%). Of the 200 patients with parathyroid lesions, 146 underwent unilateral and 54 bilateral neck exploration. 4D-CT correctly identified unilateral vs bilateral disease in 179 (89.5%) of 200. 4D-CT correctly localized parathyroid lesions in 126 of the unilateral cases (86.3%). In the re-exploration cohort, 4D-CT correctly identified unilateral vs bilateral disease in 46 (95.8%) of 48. There was no statistically significant difference in subgroups stratified by surgery type (primary or subsequent) and number of scan phases (3 or 4) (P > .56). CONCLUSIONS: 4D-CT leverages modern high-resolution CT scanning and dynamic contrast enhancement to localize abnormal parathyroid glands in patients with hyperparathyroidism of any cause and can be used for planning minimally invasive parathyroidectomy vs bilateral neck exploration.